Stage IV non-small cell lung cancer among young individuals: Incidence, presentations, and survival outcomes of conventional therapies - Cai, Jing-Sheng; Qiu, Man-Tang; Yang, Fan; Wang, Xun (Frontiers in Oncology, 2022)
Background There is a paucity of data published on the clinicopathological features and prognosis of the age <= 45 years stage IV non-small cell lung cancer (NSCLC) patients. Herein, we evaluated a large clinical series in an effort to provide a clearer picture of this population. Methods The least absolute shrinkage and selection operator (LASSO)-penalized Cox regression model was performed to identify prognostic factors. Kaplan–Meier method with a log-rank test was used to compare overall survival (OS) differences between groups. Competing risk analysis with a Fine-Gray’s test was used to analyze cancer-specific survival (CSS) differences. Propensity score matching (PSM) was used to minimize selection bias. Results Incidence-rate analyses, including 588,680 NSCLC cases (stage IV: 233,881; age <= 45 years stage IV: 5,483; and age > 45 years stage IV: 228,398) from 2004 to 2015, showed the incidence of the young stage IV NSCLC decreased over the years. In comparative analyses of clinical features and survival outcomes, a total of 48,607 eligible stage IV cases (age <= 45 years stage IV: 1,390; and age > 45 years stage IV: 47,217) were included. The results showed that although more advanced diseases were diagnosed in the age <= 45 years NSCLC group, the young patients received more aggressive treatments when compared with the age > 45 years patients. In addition, the survival rates of the young patients were superior to those of the older patients both before and after PSM. Conclusions Age <= 45 years stage IV NSCLC was a relatively small but special NSCLC subgroup. Although this population had better survival outcomes, it deserved more attention for their young age and significant socioeconomic implications.